Cryptotephra from Lipari Volcano in the eastern Gulf of Taranto (Italy) as a time marker for paleoclimatic studies. Issue 2 (March 2018) - Menke, Valerie; Kutterolf, Steffen; Sievers, Carina; Schindlbeck, Julie Christin; Schmiedl, Gerhard
Abstract: We present the first tephroanalysis based on geochemical fingerprinting of volcanic glass shards from eastern Apulian shelf sediments in the Gulf of Taranto (Italy). High sedimentation rates in the gulf are ideal for high-resolution paleoclimate studies, which rely on accurate age models. Cryptotephrostratigraphy is a novel tool for the age assessment of marine sediment cores in the absence of discrete tephra layers. High-resolution quantitative analysis of glass shard abundance in the uppermost 45 cm of a gravity core identified two cryptotephras. Microprobe analysis of glass shards supported by an accelerator mass spectrometry 14 C–based age model identified the pronounced primary cryptotephra at 36 cm bsf (below sea floor) as the felsic AD 776 Monte Pilato Eruption on the island of Lipari, whereas the thinner, mafic tephra layer at 1.5 cm bsf is associated with the AD 1944 eruption of Somma-Vesuvius. Identifying these tephra layers provides an additional, 14 C-independent, stratigraphic framework for further paleoclimatic studies allowing us to link Mediterranean climate and hydrology to orbital variation and large-scale atmospheric processes. Our results underline the importance of qualitative tephrostratigraphy in a highly geodynamic region, where solely quantitative approaches have demonstrated to bear a high potential for false correlations between tephra layers and eruptions.